1999
DOI: 10.1046/j.1365-2362.1999.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc, copper, insulin and lipids in Alzheimer's disease epsilon 4 apolipoprotein E allele carriers*

Abstract: In AD we have found a significant association between higher serum Zn, Cu and insulin concentrations and the presence of an epsilon 4 apoE allele, but only greater serum Zn concentration appears to be an independent risk factor associated with the development of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 39 publications
1
75
5
Order By: Relevance
“…Zinc also activates many kinases (including protein kinases A and C, calmodulin-dependent kinase, ribosomal S6 protein kinase, and Erk (55-62)) and may contribute to neuronal death due to transient global ischemia or traumatic brain injury (82)(83)(84)(85)(86). Increased zinc concentrations (Ͼ300 M) have been found in AD brains (87)(88)(89) and in the serum of AD patients with an APOE ⑀4 allele (90). These findings are consistent with a synergistic role of zinc and apoE4 in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc also activates many kinases (including protein kinases A and C, calmodulin-dependent kinase, ribosomal S6 protein kinase, and Erk (55-62)) and may contribute to neuronal death due to transient global ischemia or traumatic brain injury (82)(83)(84)(85)(86). Increased zinc concentrations (Ͼ300 M) have been found in AD brains (87)(88)(89) and in the serum of AD patients with an APOE ⑀4 allele (90). These findings are consistent with a synergistic role of zinc and apoE4 in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases (e.g. patients carrying ApoE e4 alleles) AD may be associated with increased circulating zinc levels (Gonzalez et al 1999). A variety of socioeconomic factors contribute to insufficient micronutrient intake in the elderly population.…”
Section: Risk Of Zinc Deficiency In the Elderlymentioning
confidence: 99%
“…For example, elevated plasma zinc is an independent risk factor for AD among e4 carriers (Gonzalez et al 1999) and the risk of AD is greater among DM2 patients that also carry the e4 allele (Peila et al 2002). Suggesting that ApoE e4 disrupts zinc homeostasis, mice expressing human e4 have decreased tissue MT levels compared to mice expressing e3 (Graeser et al 2012).…”
Section: Zinc and Insulin Signaling In Diabetes Mellitus And Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…There is new evidence suggesting that brain copper may redistribute outside the neuronal cell, leaving it relatively deficient. 7 Although past studies in man have found no differences between AD and controls in serum copper levels, [8][9][10][11] more sophisticated measurements have recently shown both an increase, [12][13][14][15] and a decrease of these levels, 16,17 thus opening a debate on a toxic or protective role of copper in AD. Results from our laboratory, though, suggest that it is the ceruloplasmin-copper relationship, rather than the level of absolute (i.e., bound and not bound to ceruloplasmin) serum copper, that may be the key issue in interpreting in vivo copper findings in AD.…”
Section: Introductionmentioning
confidence: 99%